Asuhan Keperawatan Pada Ny. J Dengan Hiperemesis Gravidarum di Ruang Nusa Indah RSUD Dr. Soeselo Kabupaten Tegal - Indri Himmatul Khoirin; Tati Karyawati; Siti Fatimah (Jurnal Anestesi, 2024)
Pregnancy is a natural and physiological process that starts from ovulation, namely the release of an egg, until the birth process. During pregnancy, special attention is needed to ensure that the baby is born healthy. Hyperemesis gravidarum is a condition where pregnant women experience nausea and vomiting that is so severe that it interferes with daily activities. This condition causes a decline in the mother's health due to dehydration. Predisposing factors for hyperemesis gravidarum include organic, psychological and endocrine aspects. Organic factors include medical conditions or disorders that can affect pregnancy. Psychological factors relate to stress or emotional problems that may affect the mother's condition. Meanwhile, endocrine factors are related to hormonal changes or hormonal imbalances during pregnancy. The author is expected to be able to create, organize and implement nursing care for Mrs. J who experienced hyperemesis gravidarum in the Nusa Indah ward at RSUD dr. Soeselo, Tegal Regency.